The relationship between learning motivation and competency-based learning with fashion designing skills for fashion design programme students at vocational college - Abd Aziz, Zaharah; Jamaluddin, Rahimah; Abdul Kadir, Suhaida (Macrothink Institute, 2021)
Technical and Vocational Education Training (TVET) highlights the mastery of skills as a key element before entering a career field. This study was conducted to identify the relationship between learning motivation and competency-based learning (CBL) and fashion designing skills for students in the Fashion Design Programme at Vocational colleges. This quantitative study with correlational research design involved 200 Diploma in Fashion Design Programme students. Simple random sampling technique was used, and data was collected through questionnaires. Findings of inferential analysis showed that fashion designing skills and learning motivation were at a moderate level with mean = 2.88 (SD = .43) and mean = 4.05 (SD = .30). Meanwhile, Competency-Based Learning recorded a mean of 3.08 with a standard deviation of .35. It was found that learning motivation had a weak relationship (r = .249, p<0.05) while CBL had a strong relationship (r = .542, p<0.05) with fashion designing skills. These findings indicate that motivation and competency-based instruction implemented during Teaching and Learning are related with mastery skill. Following that, lecturers need to ensure that the knowledge and skills imparted can be mastered by the students. It can be concluded that the management of Vocational colleges needs to provide continuous motivation to the students as well as support the lecturer to increase their knowledge on CBL in order to produce students who are highly skilled in Fashion Design.